Membangun Mental Kewirausahaan di era Digital - Zhella Rizqina Putri Rustandi; Dewi Sekar Wangi; Rayya Ahmad Putri; Sri Mulyeni (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2026)
Entrepreneurial mentality is an important aspect that must be developed by young people to face technological advancements and business competition in the digital era. The ability to think creatively and innovatively, demonstrate self-confidence, take risks, and adapt to change serves as essential capital for building sustainable businesses. This seminar aimed to provide participants with an understanding of the importance of developing an entrepreneurial mindset in the digital era and to increase their motivation to take advantage of technology-based business opportunities. The participants consisted of 70 second-semester students of University  Nasional PASIM who actively engaged in both the presentation and discussion sessions. The seminar materials covered the concept of entrepreneurial mentality, entrepreneurial characteristics, digital business opportunities, and challenges faced in the modern business environment. The results of the seminar indicated an improvement in participants’ understanding of the importance of creativity, innovation, adaptability, and courage in identifying and pursuing business opportunities. In addition, participants showed increased motivation to develop business ideas and utilize digital technology as a medium for entrepreneurship. Therefore, this seminar had a positive impact on enhancing students’ knowledge, understanding, and readiness to face challenges and seize business opportunities in the digital era.